The Pendulum Has Swung: How Do We Ensure a Life Course Approach to Immunisation in Australia? - Seale, Holly; McFadden, Kathleen; Dyda, Amalie; Kaufman, Jessica; Heywood, Anita (Frontiers in Public Health, 2022)
Rather than concentrating primarily on children and adolescents, there has been a shift in the discourse around immunisation to encompass a whole-of-life approach. Despite this acknowledgement and ongoing high burdens of vaccine preventable diseases in adults, coverage for some adult risk groups remains sub-optimal. This study aimed to explore key informants’ and stakeholders’ perceptions of factors impacting provision of immunisation programs for Australian adults and to identify strategies to promote acceptance and uptake. Semi-structured telephone interviews were undertaken with people involved in adult immunisation program delivery, advocacy, policy or research between September 2020 and June 2021. Transcripts were inductively analysed, with the resulting themes categorized into the five influences on vaccination gaps that have informed program planning in other countries: Access, Affordability, Awareness, Acceptance and Activation. Participants spoke of improvements in the provision of vaccines to adults, however, ongoing challenges persisted. Participants agreed that the focus or emphasis of policies and the promotion/communication strategies has been on childhood vaccination in Australia, however there is a sense that the “pendulum has swung”. These included understanding of eligibility amongst the Australian population and the reluctance of some health providers to dedicate time to exploring immunisation needs with adult patients. In comparison to the childhood vaccination program, there has been a lack of data available on coverage for adult vaccines on the national immunisation program. This has contributed to the ongoing challenges of identifying and promoting certain vaccines. At a government level, questions were raised about why the Australian government has never set an aspirational target for adult vaccination (i.e., influenza or pneumococcal) coverage. While significant improvements have been made in adult immunisation uptake, there are still gaps across the program. While the system remains under stress because of the COVID-19 pandemic, it is not appropriate to implement any additional programs. There needs to be strong commitment to establish the value of adult vaccination in the eyes of community members, policy makers and healthcare professionals. Having a national adult immunisation strategic plan would help advance action.